Bakti Sosial Dosen, Alumni, dan Himpunan Mahasiswa Teknik Elektro Fakultas Teknik dan Komputer Universitas Harapan Medan ke Panti Asuhan Putra Muhammadiyah Jl. Amaliun Gg. Umanat Kota Medan - Indra Roza; Ahmad Yanie; Yussa Ananda; Lisa Adriana Srg; Agus Almi Nst; Dara Safitri (Jurnal TUNAS, 2022)
Orphanages or facilities where children who can't afford to gather or are often called orphans are also called social institutions where the aim is to protect and educate them so that they can live a better and more secure life. Even though their lives must receive support and assistance from benefactors and people who have great social concern for the continuity of their education and life in the future. The Putra Muhammadyah Orphanage which is located on Jalan Amalun Gang Umanat, Medan City, North Sumatra, has been established in 1964 and has a good status with a score of 344. During this social service visit, we were attended by lecturers, alumni, students, and also the electrical engineering student association. Hope University Medan. Where on our visit we donated rice in the form of approximately one hundred kilograms (100 kilos). The administrators and residents of the orphanage were very enthusiastic and happy to receive us.